SARS-CoV-2 is localized in cardiomyocytes: a postmortem biopsy case. (October 2021) - Nakamura, Yoshihiko; Katano, Harutaka; Nakajima, Noriko; Sato, Yuko; Suzuki, Tadaki; Sekizuka, Tsuyoshi; Kuroda, Makoto; Izutani, Yoshito; Morimoto, Shinichi; Maruyama, Junichi; Koie, Megumi; Kitamura, Taisuke; et al.
Highlights: Pathogenesis of acute cardiac injury with COVID-19 remains unknown The patient experienced shock due to takotsubo cardiomyopathy with COVID-19 SARS-CoV-2 antigen was detected in cardiomyocytes by immunostaining SARS-CoV-2 detection in cardiomyocytes suggests an association with cardiac injury Abstract: A 72-year-old patient was admitted to the intensive care unit due to acute respiratory distress syndrome caused by COVID-19. On day 20, the patient experienced shock. The electrocardiogram showed ST segment elevation in leads V3–V6 and severe left ventricular dysfunction with an ejection fraction of 35%–40%. The left ventricle showed basal hypokinesis and apical akinesis, while the creatine kinase level was normal, indicating Takotsubo cardiomyopathy. On day 24, the patient died of multiple organ failure. In post-mortem biopsy, SARS-CoV-2 antigen was detected in cardiomyocytes by immunostaining. Moreover, SARS-CoV-2 RNA was detected in heart tissue. We need to further analyse the direct link between SARS-CoV-2 and cardiomyocytes.